Efficacy of PD-1 blockade plus chemotherapy in patients with oncogenic-driven non-small-cell lung cancer - Haowei Wang; Lei Cheng; Jian Chen; Peixin Chen; Zhuoran Tang; Qianyi Wang; Ying Ma; Chao Zhao; Xuefei Li; Tao Jiang; Fei Zhou; Xiaoxia Chen; et al. (Cancer Immunology, Immunotherapy)
Abstract Background PD-1 blockade plus chemotherapy has become the first-line standard of care for patients with advanced non-small-cell lung cancer (NSCLC) without oncogenic drivers. Oncogenic-driven advanced NSCLC showed limited response to PD-1 blockade monotherapy or chemotherapy alone. Whether NSCLC patients with oncogenic drivers could benefit from PD-1 blockade plus chemotherapy remains undetermined. Methods Three hundred twelve NSCLC patients with at least one oncogenic driver alteration received PD-1 plus chemotherapy or each monotherapy were retrospectively identified. Objective response rate (ORR), progression-free survival (PFS), and overall survival (OS) were compared to evaluate the therapeutic outcomes differences among patients with different oncogenic drivers. Results One hundred sixty-two patients received PD-1 blockade plus chemotherapy, 57 received PD-1 blockade monotherapy and 93 received chemotherapy alone were included. Oncogenic driver mutations including KRAS (31.4%), EGFR (28.8%), HER2 (14.7%), BRAF (10.6%), RET (7.4%), and other mutations (7.1%) were identified. Patients with oncogenic drivers who received PD-1 blockade plus chemotherapy had significantly better outcomes compared to those received PD-1 blockade or chemotherapy alone (ORR: 51% vs. 18% vs. 25%, P < 0.001; median PFS: 10.0 [95% CI: 8.9–12.6] vs. 3.7 [95% CI: 2.9–5.1] vs. 5.3 [95% CI: 4.5–6.2] months, P < 0.001; median OS: 26.0 [95% CI: 23.0–30.0] vs. 14.3 [95% CI: 9.6–19.8] vs. 16.1 [95% CI: 11.6–21.9] months, P < 0.001). The superior efficacy was consistently found in separate analyses for patients received first-line and second/third line treatments. Among individual gene alterations, patients with KRAS, EGFR, or BRAF mutations treated with PD-1 blockade plus chemotherapy achieved markedly improved PFS and OS than those received PD-1 blockade or chemotherapy alone. Multivariate Cox regression analysis revealed that PD-1 blockade plus chemotherapy was independently associated with better PFS and OS. Conclusion PD-1 blockade plus chemotherapy demonstrated superior efficacy than PD-1 blockade monotherapy or chemotherapy alone in patients with oncogenic-driven advanced NSCLC, particularly in KRAS, EGFR and BRAF subgroups. These findings suggest that PD-1 blockade plus chemotherapy may be considered as an optional treatment option for patients without available targeted therapies.